Internal audit quality dimensions and organizational performance in Nigerian federal universities: the role of top management support - Bello, Suleiman Mohammed (The Academy of Business and Retail Management (ABRM), 2018)
The study examines the moderating effects of top management support in the relationship between internal quality dimensions and organizational performance in Nigerian federal universities. The study employed a sample of internal audit staff at senior level from 40 federally owned universities in Nigeria where 400 samples have been drawn for the analysis. Questionnaire instrument was used in generating the data having subjected to Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) aimed at establishing underlying dimensions. The data was collected and analysed using inferential statistics and the findings revealed that interaction of internal audit competence, internal audit independence, and internal audit size, with top management support significantly and positively influence organization performance of Nigerian federal universities. The findings provide ground for new policy initiatives to strengthen internal audit and enriched the literature by providing the moderating effect of top management support as instrumental to organizational performance. It is therefore recommended that internal audit competence internal audit independence and internal audit size should be given more attention and mechanism through which these qualities can be employed and sustained for more internal audit service delivery and efficiency in Nigerian federal universities.